Mechanosignaling in the vasculature: emerging concepts in sensing, transduction and physiological responses - Chatterjee, Shampa (2015)
Cells are constantly exposed to mechanical forces that play a role in modulating cellular structure and function. The cardiovascular system experiences physical forces in the form of shear stress and stretch associated with blood flow and contraction, respectively. These forces are sensed by endothelial cells and cardiomyocytes and lead to responses that control vascular and cardiac homeostasis. This was highlighted at the Pan American Physiological Society meeting at Iguassu Falls, Brazil, in a symposium titled “Mechanosignaling in the Vasculature.” This symposium presented recent research that showed the existence of a vital link between mechanosensing and downstream redox sensitive signaling cascades. This link helps to transduce and transmit the physical force into an observable physiological response. The speakers showcased how mechanosensors such as ion channels, membrane receptor kinases, adhesion molecules, and other cellular components transduce the force via redox signals (such as reactive oxygen species and nitric oxide) to receptors (transcription factors, growth factors, etc.). Receptor activated pathways then lead to cellular responses including cellular proliferation, contraction, and remodeling. These responses have major relevance to the physiology and pathophysiology of various cardiovascular diseases. Thus an understanding of the complex series of events, from the initial sensing through the final response, is essential for progress in this field. Overall, this symposium addressed some important emerging concepts in the field of mechanosignaling and the eventual pathophysiological responses.